Utopia as a reinforcement of tourist experiences - Christou, Prokopis A.; Farmaki, Anna (My University, 2019)
Utopia (οὐ and τόπος) fundamentally relates to a fictional society (More, 1516), an escapist world and unreal space (Podoshen, Venkatesh, & Jin, 2014). Foucault distinguishes spaces into utopias which have no real space and heterotopias which are “other” spaces; worlds within worlds, such as prisons (Foucault & Miskowiec, 1986). Despite such cosmologies, utopia has been associated with non-mythical settings; the region of Arcadia was depicted from ancient times as a “utopian” setting, despite the fact that the particular place actually exists, alluding to a vision of pastoralism and harmonic coexistence with nature. Such idealistic topoi (places), have been allied with mythical creatures (e.g. Nymphs). Likewise, utopic places of natural exquisiteness have been linked with “elves” in the case of Tolkien’s legendarium (Tolkien, 1977). Utopia has been examined within different contexts, such as psychedelic utopia (Beauchamp, 1990) and esoteric philosophical utopia which has been an avenue of escape from ugly reality (Manuel & Manuel, 1979). Even so, it has troubled early philosophers, and remains a perplexed notion subject to different interpretations, despite its link and significance to topoi. The majority of place-tourism research has been dedicated to the examination of particular sites/venues and certain activities offered within places (Granås, 2018) and their effects on individuals (Pearce, 2012). Other recent studies have focused on places from a tourism perspective, such as on their consumption (Rakić & Chambers, 2012). Nonetheless, fantasies, mythologized imaginaries of otherness and discourses about peoples and places, often act as the motor setting tourism in motion (Salazar and Graburn, 2014, Amirou, 1995). This particular exploratory study (Christou, 2018) which took place in Iceland (June 2018), attempts to explore the extent to which a “utopic” experience is promoted by tourism stakeholders, and to understand how visitors perceive such initiatives. Iceland, with its unique morphology and natural phenomena, has long been associated with utopic place manifestations; Annotations portray an idiomorphic physical setting, a legendary land of immortals fighting in lava-fields and a playground of álfar- elves (Hafstein, 2000), or huldufólk (Sontag, 2007) who pertain to place secrecy.
Keywords: Utopia; Utopic; Tourism stakeholders; Exploratory study; Iceland